Antioxidant Responses in Chromium-Stressed Maize as Influenced by Foliar and Root Applications of Fulvic Acid - Farwa Iftikhar; Asma Zulfiqar; Atif Kamran; Ammara Saleem; Muhammad Zeeshan Arshed; Usman Zulfiqar; Ivica Djalovic; P. V. Vara Prasad; Walid Soufan (Scientific Reports)
Abstract Maize (Zea mays L.) faces significant challenges to its growth and productivity from heavy metal stress, particularly Chromium (Cr) stress, which induces reactive oxygen species (ROS) generation and damages photosynthetic tissues. This study aimed to investigate the effects of fulvic acid (FA) application, via foliar spray or root irrigation, on mitigating chromium stress in maize by evaluating its impact on antioxidant activity and growth parameters. Two maize varieties, P3939 and 30Y87, were subjected to chromium stress (CrCl3·6H2O) at concentrations of 300 µM and 100 µM for a duration of 5 weeks. The experiment was conducted in a wire house under natural environmental conditions at the Seed Centre, Institute of Botany, University of the Punjab, Lahore, Pakistan. Physiological assessments included electrolyte leakage, chlorophyll pigment content, malondialdehyde (MDA) levels, and activities of antioxidant enzymes such as catalase (CAT), ascorbate peroxidase (APX), and guaiacol peroxidase (GPX) in maize leaves. Growth parameters were also monitored. The results revealed that chromium stress significantly reduced chlorophyll content and increased oxidative stress, as evidenced by elevated MDA levels and electrolyte leakage. However, FA application notably mitigated these effects: chlorophyll content improved by 15%, and MDA levels decreased significantly. Irrigation with FA was particularly effective, reducing MDA levels by 40% compared to the 300 µM chromium treatment. Furthermore, while chromium stress enhanced antioxidant enzyme activities, FA application further boosted total soluble protein levels and antioxidant enzyme activities under stress conditions. In conclusion, FA application demonstrates potential in improving maize tolerance to heavy metal stress by enhancing the antioxidant defense system and preserving photosynthetic pigments. These findings highlight FA’s promise as a practical strategy for mitigating the negative impacts of chromium stress on maize, promoting sustainable agricultural practices in contaminated environments.